2021
DOI: 10.2478/rtuect-2021-0049
|View full text |Cite
|
Sign up to set email alerts
|

Towards Green and Smart Seaports: Renewable Energy and Automation Technologies for Bulk Cargo Loading Operations

Abstract: In 2018, 4.1 billion tonnes of freight and 437 million passengers passed through the 1200 European ports. This dimension of geographically concentrated activities is the rationale that ports are characterised by a high-energy demand and a high share of emissions. Driven by a growing awareness for a cleaner environment, a stronger focus on sustainability and intensified environmental regulations, ports are forced to take responsibility when it comes to environmental issues. As a response, in recent studies, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 31 publications
0
4
0
6
Order By: Relevance
“…A partir de estas citas, se puede concluir que la automatización en los puertos inteligentes no solo busca aumentar la eficiencia y reducir costos, sino también mejorar la calidad del servicio, aumentar la seguridad y contribuir a la sostenibilidad ambiental [15]. La capacidad de los puertos automatizados para densificar sus operaciones y utilizar de manera óptima el espacio disponible puede llevar a la creación de terminales más compactos y eficientes [13].…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A partir de estas citas, se puede concluir que la automatización en los puertos inteligentes no solo busca aumentar la eficiencia y reducir costos, sino también mejorar la calidad del servicio, aumentar la seguridad y contribuir a la sostenibilidad ambiental [15]. La capacidad de los puertos automatizados para densificar sus operaciones y utilizar de manera óptima el espacio disponible puede llevar a la creación de terminales más compactos y eficientes [13].…”
Section: Resultsunclassified
“…En lo que respecta a la implementación, un ejemplo destacado es el caso de Asia Pacífico, que se ha caracterizado por ser una de las regiones que menos ha tardado en implementar la automatización en sus terminales [13]. Asimismo, dichas operaciones, especialmente la de manejo de contenedores, han demostrado mayor eficiencia energética debido a la agilización de las operaciones de carga y la reducción de la necesidad de mano de obra, lo que también ha resultado en una disminución de costos y precios, generando así una ventaja competitiva para el puerto [15]. Otra de las ventajas obtenidas por la aplicación de esta tecnología es la protección a los trabajadores fronterizos eliminando los riesgos de contacto innecesarios [16].…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Chen, Huang, et al, 2019) According to modern perspectives from recent literature, the dialectical and tightly integrated relationship between the concept of green port and smart port is very clear. In the operation and development strategy of ports, green ports and smart ports always go hand in hand and integrate into each other (Philipp et al, 2021). The main goals of sustainable development in a port are the unification of green development goals with smart methods and infrastructure.…”
Section: Concepts and Characteristics Of Green Portmentioning
confidence: 99%
“…CO 2 taxation is an essential instrument for supporting green investments in the European Union since it internalizes environmental costs into energy production. Philipp R. et al [55] investigated the financial performance of energy-saving investments under the frame conditions of increasing CO 2 taxation schemes. They revealed that in the long-term, RE investments might become economically favorable.…”
mentioning
confidence: 99%